1999
DOI: 10.1109/55.748907
|View full text |Cite
|
Sign up to set email alerts
|

RTD/CMOS nanoelectronic circuits: thin-film InP-based resonant tunneling diodes integrated with CMOS circuits

Abstract: Abstract-The combination of resonant tunneling diodes (RTD's)and complementary metal-oxide-semiconductor (CMOS) silicon circuitry can offer substantial improvement in speed, power dissipation, and circuit complexity over CMOSonly circuits. We demonstrate the first integrated resonant tunneling CMOS circuit, a clocked 1-bit comparator with a device count of six, compared with 21 in a comparable all-CMOS design. A hybrid integration process is developed for InP-based RTD's which are transferred and bonded to CMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Devices employing the tunnelling effect have been extensively studied and are now being considered for memory devices [4]. Furthermore, it has been demonstrated that III-V semiconductor tunnelling devices can be integrated with silicon CMOS technology, and that CMOS electronics can drive tunnelling devices [5]. The physics and progress in electronic applications of resonant tunnelling devices (RTDs) have recently been reviewed in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Devices employing the tunnelling effect have been extensively studied and are now being considered for memory devices [4]. Furthermore, it has been demonstrated that III-V semiconductor tunnelling devices can be integrated with silicon CMOS technology, and that CMOS electronics can drive tunnelling devices [5]. The physics and progress in electronic applications of resonant tunnelling devices (RTDs) have recently been reviewed in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Optical links between fibre and OEIC [23][24][25] HBTs, RTDs Adhesive bonding of BCB, which also serves as a dielectric separation to the lossy Si Small thin-film modules for highfrequency handling on Si IC [26][27][28] wafers are fragile and available only in small sizes (with a price premium of US $30/sq.in). By implementing wafer bonding technology low-cost and large-area carrier substrates could be used to host InP-based materials.…”
Section: Emitters/ Detectorsmentioning
confidence: 99%
“…Indirect bonding technologies that are easier to use include adhesive bonding or eutectic bonding, where intermediate layers of polymers [20][21][22][23][24][25][26][27][28]36], spin-on-glasses [37] and metals [17][18][19]38]. These methods may ease bonding of dies to wafers, reducing the amount of III-V material to be used on a Si wafer.…”
Section: Indirect Inp-to-si Wafer Bondingmentioning
confidence: 99%
“…Compared to previous attempts to produce tunneling devices, high precision growth now gives much more control over device characteristics which are crucially dependent on layer thickness and tunneling devices are now being considered as memory devices [1] and a new logic family has been proposed [2]. Furthermore, it has been demonstrated that III-V semiconductor tunneling devices can be integrated with silicon CMOS technolgy and that tunneling devices can be driven by CMOS logic levels [3]. The physics and progress in electronic applications of Resonant Tunneling Diodes (RTDs) have recently been reviewed in [4].…”
Section: Introductionmentioning
confidence: 99%